2021
DOI: 10.1136/bcr-2020-236469
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatosis with polyangiitis presenting with unilateral facial nerve palsy and nasal septum perforation

Abstract: Granulomatosis with polyangiitis (GPA) is a necrotising vasculitis of unknown cause that has several systemic manifestations. The disease is characterised by the classical triad involving acute inflammation of the upper and lower respiratory tracts with renal involvement. However, the disease pathology can involve the central nervous system. This case report presents a case of GPA with facial nerve palsy as the first manifestation of the disease, which has been rarely reported in the medical literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…There are cases reported with episcleritis and conjunctivitis as the initial clinical features of GPA [16 , 17] . A case of septal perforation associated with unilateral facial nerve palsy has also been reported [18] . This case is a rare presentation of GPA where a patient has been mistakenly diagnosed with sinonasal polyposis due to sinonasal disease seen on CT scans and overlapping clinical features.…”
Section: Discussionmentioning
confidence: 97%
“…There are cases reported with episcleritis and conjunctivitis as the initial clinical features of GPA [16 , 17] . A case of septal perforation associated with unilateral facial nerve palsy has also been reported [18] . This case is a rare presentation of GPA where a patient has been mistakenly diagnosed with sinonasal polyposis due to sinonasal disease seen on CT scans and overlapping clinical features.…”
Section: Discussionmentioning
confidence: 97%
“…ANCA-positive vasculitides like granulomatosis with polyangiitis are systemic diseases that affect multiple organs within the body. Granulomatosis with polyangiitis often presents initially with ear-nose-throat involvement (e.g., rhinitis, sinusitis, mastoiditis, saddle nose deformity, epistaxis) and can also include lung involvement (e.g., pulmonary nodules, pleural effusion) causing cough, dyspnea, wheezing, and hemoptysis [ 7 ]. A study by Cannady et al reported NSP in 33% of their patients with granulomatosis with polyangiitis, commonly presenting as part of the initial symptomology [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Renal involvement is not a common primary presentation; however, 77-85% of patients ultimately develop kidney disease with signs including proteinuria and red blood cell casts. This can rapidly evolve to end-stage renal disease [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] Neurological manifestations are present in 20% to 50% of GPA cases, with central nervous system involvement in 10% of patients. [ 2 , 3 ] In hypertrophic dura meningitis, GPA with headache is typical. [ 4 ] In this case, cerebral magnetic resonance (MR) enhancement revealed no meningeal thickening, to our knowledge, this manifestation had not been found previously.…”
Section: Introductionmentioning
confidence: 99%